Entrepreneurial Outcomes and Organisational Performance through Business Coaching - Mihaela Dobrea; Irina Maiorescu (Amfiteatru Economic Journal, 2015)
The hereby article aims to address the main question of whether organisational performance is directly or indirectly enhanced by business coaching. The research integrates a quantitative study having as major purpose the investigation of the manner in which business coaching contributes to corporation growth in start-up firms and developing companies. The primary objective of the research is to quantitatively determine the effects enhanced by business coaching on company performance and growth of organisational incomes. SME growth and coaching impact are studied through inter-relationships between distinctive company characteristics (such as: industry category, company maturity, number of employees), entrepreneur features (among which can be mentioned: leader age, nominal gender, studies), and entrepreneur character (for instance: locus of control at work, selfefficacy in the work place). The comparison is made between two types of entrepreneurs: the ones who have received business coaching previously with entrepreneurs with no prior business coaching experience, except the one after which research is performed. The research concludes that business coaching has a great impact on the development of entrepreneurs' locus of control and self-efficacy, these leading to organisational growth.
Keywords: M12; M53; I25; 330; Business Coaching; Executive Coaching; Financial Performance; Income; Entrepreneurial; Control; Self-efficacy